Non-coding RNA-mediated high expression of SFXN3 as a prognostic biomarker associated with paclitaxel resistance and immunosuppressive microenvironment in head and neck cancer - Chen, Kailin; Gong, Sha; Fang, Xueliang; Li, Qian; Ye, Mingliang; Li, Junyan; Huang, Shengyan; Zhao, Yuheng; Liu, Na; Li, Yingqin; Ma, Jun (Frontiers in Immunology, 2022)
Chemoresistance is the leading cause of poor prognosis in head and neck squamous cell carcinoma (HNSC); however, promising biomarkers to identify patients for stratified chemotherapy are lacking. Sideroflexin 3 (SFXN3) is an important mitochondrial serine transporter during one-carbon metabolism, which is involved in the proliferation of cancer cells. However, the specific role of SFXN3 in HNSC remains unknown. In this study, we performed expression and survival analysis for SFXN3 in pan-cancer using data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) and found that SFXN3 served as a potential oncogene in HNSC. Notably, SFXN3 expression was found to be positively associated with enriched tumor-infiltrating macrophages, other immune suppressive cells, and immune checkpoint expression and resistance to paclitaxel. Gene, clinical and immune variables included in the univariate and multivariate analysis showed SFXN3 expression was an independent risk factor. Moreover, the LINC01270/hsa-miR-29c-3p/SFXN3 axis was identified as the most likely upstream noncoding RNA-related pathway of SFXN3 in HNSC using bioinformatic analysis, expression analysis, correlation analysis, and survival analysis. Taken together, our findings demonstrated that noncoding RNA-mediated high expression of SFXN3 is a prognostic biomarker and is associated with the immunosuppressive microenvironment in HNSC.